Maternal interpersonal affiliation is associated with adolescents' brain structure and reward processing - Schneider, Sophia; Banaschewski, Tobias; Flor, Herta; Nees, Frauke; Rietschel, Marcella; Struve, Maren (Translational Psychiatry, 2012)
Considerable animal and human research has been dedicated to the effects of parenting on structural brain development, focusing on hippocampal and prefrontal areas. Conversely, although functional imaging studies suggest that the neural reward circuitry is involved in parental affection, little is known about mothers' interpersonal qualities in relation to their children's brain structure and function. Moreover, gender differences concerning the effect of maternal qualities have rarely been investigated systematically. In 63 adolescents, we assessed structural and functional magnetic resonance imaging as well as interpersonal affiliation in their mothers. This allowed us to associate maternal affiliation with gray matter density and neural responses during different phases of the well-established Monetary Incentive Delay task. Maternal affiliation was positively associated with hippocampal and orbitofrontal gray matter density. Moreover, in the feedback of reward hit as compared with reward miss, an association with caudate activation was found. Although no significant gender effects were observed in these associations, during reward feedback as compared with baseline, maternal affiliation was significantly associated with ventral striatal and caudate activation only in females. Our findings demonstrate that maternal interpersonal affiliation is related to alterations in both the brain structure and reward-related activation in healthy adolescents. Importantly, the pattern is in line with typical findings in depression and post-traumatic stress disorder, suggesting that a lack of maternal affiliation might have a role in the genesis of mental disorders.